The Social Workers Challenges on Community Welfare in Ungogo Community, Nigeria - Kehinde Adekunle Aliyu; Jamaluddin Mustaffa; Norruzeyati Che Mohd Nasir (Department of Government Studies Universitas Muhammadiyah Makassar, 2017)
The role of social workers in a community cannot be overemphasised by any mean, for the life span of any community depends on the quality of the social workers. The aim of this work is to affirm the roles of social workers in helping the community welfare. Qualitative research design was adopted for the work. Data collected with the Interview Schedule for Officials of the Federal Road Safety Corps and Interview Guide for selected group of people. This was administered to 30 respondents, which comprises both male and female in the Ungogo community. The purpose of the study was to examine the roles of social workers, in line with improved standards of living, sustained economic development and expansion of trade and economic relations in the community; enhanced levels of international competitiveness in the areas of community welfare, organization for increased productivity of people in the community. It common knowledge every individual strife to be the best when receive the necessary or adequate encouragement. To these extents, such a person bears some responsibilities even if passively so as a member. The implication of this work is to contribute to social change by informing social worker on their challenges and responsibilities ahead of them in the community.